Settlement of Tax Disputes Through the Application of the Principle of Equity - Rasji; Farell David Trawocoadji (JILPR Journal Indonesia Law and Policy Review, 2023)
Tax is a mandatory financial contribution or obligation where individuals are required to allocate a portion of their wealth or income to the government. This process allows the government to access some of society's financial resources for the benefit of the country as a whole. In tax collection, the basic principle of equality is applied. This principle underlines that taxation must be applied impartially, without discrimination. People in similar circumstances should face the same tax rates, and there should be no deviation from applicable laws in tax collection. Fulfillment of this principle guarantees a tax system that prioritizes justice, and all forms of tax collection are carried out in accordance with legal limits, thus providing legal certainty for taxpayers. The research method used is a normative juridical approach, and the data collected in this research is secondary data.